Peran Advokat Dalam Pengembangan Ekonomi Syariah Khususnya di Bidang Perbankan Syariah - H.M. Siregar (Law Faculty of Universitas Bandar Lampung, 2011)
The Advocate Role 117 Sharia Economic Developmental, a especial of Islamic Sharia Banking, in the context of increasingly widespread Islamic economy these days, it is much needed role of the Advocate. The Advocates help solving the problem; giving and serving legal advice, among others in the field of Islamic banking, Islamic insurance, Islamic mutual funds, and broker sharia; creating a legal audit and legal opinion in preparation for the establishment, mergers and acquisitions sharia, including for the purpose of borrowing money and investing; conducting advocacy in the forum court; creating of legal drafting and Islamic business contracts, representing a company attorney at sharia arbitration forum either institutional or ad hoc or on the forum Alternative Settlement Issues (alternative dispute resolution), for example: mediation, consultation, negotiation, conciliation and expert evaluation.